Patai's Chemistry of Functional Groups 2011
DOI: 10.1002/9780470682531.pat0445
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Organocopper Compounds

Abstract: Introduction Formation of C  C Bonds Formation of C  N Bonds Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The synthetic chemistry of organocuprates started to evolve rapidly in 1966, when House and co-workers showed that the Gilman cuprate Me 2 CuLi undergoes a conjugate addition reaction to an enone, which suggests that this and related species are the true reactive species of the Kharasch conjugate addition reaction. Soon after this report, Corey and Posner discovered substitution reactions between the Gilman reagent and alkyl, alkenyl, allyl, or aryl halides, and Whitesides and co-workers reported oxidative homocoupling of Gilman cuprates using molecular oxygen. , Important initial developments of fundamental transformations, including the substitution reactions of alkyl, alkenyl, and aryl halides, alkyl tosylates, epoxides, , and allyl, , propargyl, and acyl electrophiles, , and addition reactions to electron-deficient alkynes and unactivated alkynes, were achieved by the mid-1970s. , …”
Section: Introductionmentioning
confidence: 99%
“…The synthetic chemistry of organocuprates started to evolve rapidly in 1966, when House and co-workers showed that the Gilman cuprate Me 2 CuLi undergoes a conjugate addition reaction to an enone, which suggests that this and related species are the true reactive species of the Kharasch conjugate addition reaction. Soon after this report, Corey and Posner discovered substitution reactions between the Gilman reagent and alkyl, alkenyl, allyl, or aryl halides, and Whitesides and co-workers reported oxidative homocoupling of Gilman cuprates using molecular oxygen. , Important initial developments of fundamental transformations, including the substitution reactions of alkyl, alkenyl, and aryl halides, alkyl tosylates, epoxides, , and allyl, , propargyl, and acyl electrophiles, , and addition reactions to electron-deficient alkynes and unactivated alkynes, were achieved by the mid-1970s. , …”
Section: Introductionmentioning
confidence: 99%
“…Related reactions of aryl radicals and [CuCF 3 ] to form aryl–CF 3 bonds have been reported 23. There also exists the possibility that intermediate C may arise via carbocupration24 processes with [CuCF 3 ] under oxidative conditions. For instance, aryne A may undergo carbocupration with a [Cu(CF 3 ) n ]25 species to give C .…”
Section: Resultsmentioning
confidence: 98%
“…We have indeed recently shown that copper acetylides can be easily activated in the presence of molecular oxygen and simple organic ligands and transfer their alkyne subunit to a wide range of heteronucleophiles following an oxidative umpolung strategy. , On the basis of the success met with this strategy, we envisioned that they might also be suitable reagents for the direct room-temperature alkynylation of (hetero)arenes possessing relatively acidic C–H bonds such as azoles and polyfluoroarenes, a strategy that was supported by results from the Knochel group who demonstrated the possibility of an oxidative copper-mediated cross-coupling between alkynyl lithium and aryl magnesium reagents…”
mentioning
confidence: 92%